Expression and purification of Cry8Da recombinant protein against coleopteran insects of bacillus thuringiensis in E. Coli - Thi Minh Thanh, Le; Thi Hue, Nguyen; Duy Quy, Tran; Dinh Binh, Ngo (Vietnam Journal of Science and Technology, 2017)
Bacillus  thuringiensis  (Bt)  is  widely  used  in  agriculture  for  pest  control  against Lepidoptera, Diptera  and Coleoptera  orders.  It  is  very  difficult  to  control  of Coleoptera  pests such  as  larvae  of  Scarabaeidae  family,  which  damage  the  roots  of  tusf  grass  and  other horticultural and agricultural plants, because they are living in soil where sprayable insecticidal formulation  is  hard  to  reach  the  target  insects.  The Cry8-type  proteins  specified  to  larvae  of scarab  beetles.  The  Cry8-type  proteins  are  insecticidal  to  larvae  of  scarab  beetles.  Bacillus thuringiensis  Cry8D  (Cry8Da,  Cry8Db)  insecticidal  proteins  are  unique  among  Cry8  family protein  in  terms  of  its  insecticidal  activity  against  larvae  and  adult  Scarab  beetles,  such  as Japanese  beetle  (Anomala  cuprea,  Popillia  japonica).  In  this  study,  cry8Da  gene  encoding nature protein Cry8Da, which were isolated in Vietnam, was expressed in E. coli. The 2031 bp of cry8Da gene  is digested from recombinant plasmid pGEM-cry8Da with BamHI và sacI and ligated  into  pET32a(+)  vector  treated  with  the  same  enzymes.  The  recombinant  plasmids pET32a(+)-cry8Da  were  expressed  in  BL21(DE3)LysS  strain  under  induction  of  IPTG.  The highest level for expression of Cry8Da recombinant E. coli has been obtained after induction by 1 mM IPTG at 30 0C for 4 hrs. Recombinant Cry8Da protein has molecular mass about 96 kDa and  purified  by  Ni(2+)  affinity  chromatography  column,  concentration  0,45  mg/ml  after purification. The expressed  recombinant Cry8Da protein was confirmed by Western blot using anti-Cry8Da antibody.